Single gauge bosons production in the high-energy lepton-photon collisions processes - Shershan, Ivan A.; Shishkina, Tatiana V. (Journal of the Belarusian State University. Physics, 2019)
The different lepton-photon interactions was considered to search for deviations from the Standard Model. In particular,lepton-photon interactions are discussed as atool for studying neutrino oscillations and lepton flavor violation. Analytic Lorentz invariant expressions for the differential cross sections of the single gauge bosons production as aresult of lepton-photon collisions were obtained and analyzed. The total cross sections numerical analysis of the processes was performed. The kinematics limits for obtaining of deviations from the Standard Model were determined and discussed to get of differences depending on interacting leptons. It is shown that the search for «new physics» in the lepton sector of the Standard Model is best done by studying the differential cross sections for the neutral gauge bosons production at maximum of scattering angles. The differential cross sections for the charged gauge bosons production in the case of the different types of leptons interactions with photons can be used to search for deviations from the Standard Model in the entire kinematics region.